MAPK phosphatase AP2C3 induces ectopic proliferation of epidermal cells leading to stomata development in Arabidopsis. - Julija Umbrasaite; Alois Schweighofer; Vaiva Kazanaviciute; Zoltan Magyar; Zahra Ayatollahi; Verena Unterwurzacher; Chonnanit Choopayak; Justyna Boniecka; James A H Murray; Laszlo Bogre; Irute Meskiene (PLoS ONE)
In plant post-embryonic epidermis mitogen-activated protein kinase (MAPK) signaling promotes differentiation of pavement cells and inhibits initiation of stomata. Stomata are cells specialized to modulate gas exchange and water loss. Arabidopsis MAPKs MPK3 and MPK6 are at the core of the signaling cascade; however, it is not well understood how the activity of these pleiotropic MAPKs is constrained spatially so that pavement cell differentiation is promoted only outside the stomata lineage. Here we identified a PP2C-type phosphatase termed AP2C3 (Arabidopsis protein phosphatase 2C) that is expressed distinctively during stomata development as well as interacts and inactivates MPK3, MPK4 and MPK6. AP2C3 co-localizes with MAPKs within the nucleus and this localization depends on its N-terminal extension. We show that other closely related phosphatases AP2C2 and AP2C4 are also MAPK phosphatases acting on MPK6, but have a distinct expression pattern from AP2C3. In accordance with this, only AP2C3 ectopic expression is able to stimulate cell proliferation leading to excess stomata development. This function of AP2C3 relies on the domains required for MAPK docking and intracellular localization. Concomitantly, the constitutive and inducible AP2C3 expression deregulates E2F-RB pathway, promotes the abundance and activity of CDKA, as well as changes of CDKB1;1 forms. We suggest that AP2C3 downregulates the MAPK signaling activity to help maintain the balance between differentiation of stomata and pavement cells.